A review of the open-access scenario in Afghanistan. Issue 4 (18th November 2019) - Dandawate, Vrushali Sainath; M., Dhanamjaya
Abstract : Purpose: Open access movement is getting increased in Asia and the Pacific and has been started in the form of subject gateways, informal collections of articles on web pages and directories. Many Asian countries adopted the transition to Open Access journals and full-text repositories and digital libraries. Open access also helps to underprivilege countries to spread their research output. But third-world Islamic countries are far away from open access and its implementations. The purpose of this paper is to focus on open-access e-resource development in Afghanistan. Design/methodology/approach: The data were complemented by documentary analysis, and information retrieved from open-access databases like DOAR, DOAJ and OER Sites. Findings: The paper provides information about open-access development in Afghanistan and also focuses on the challenges for spreading OA awareness in Afghanistan. It suggests that how local people and universities can help to spread open-access movement. Social implications: This paper gives an idea about the educational system and other resources available in Afghanistan. Originality/value: This paper fulfills an identified need to study open-access development and status in Afghanistan.